Bbmsn2 acts as a pH‐dependent negative regulator of secondary metabolite production in the entomopathogenic fungus Beauveria bassiana. (17th July 2014) - Luo, Zhibing; Li, Yujie; Mousa, Jarrod; Bruner, Steven; Zhang, Yongjun; Pei, Yan; Keyhani, Nemat O.
Summary Fungal secondary metabolites are chemical compounds important for development, environmental adaptation and for potential biotechnological and pharmaceutical applications. Oosporein, a red‐pigmented benzoquinone, produced by many fungal insect pathogenic Beauveria spp., shows remarkable functional diversity, displaying antimicrobial, antiviral and even anti‐proliferative activities. A homologue of the msn2/seb1 transcription factor was identified in a Beauveria bassiana random T‐DNA insertion library. Targeted gene‐knockout of Bbmsn2 resulted in reduced growth and increased sensitivity to Calcofluor White, H2O2 and Congo Red. However, when normalized to growth at 26°C, the ΔBbmsn2 mutant was more tolerant to high temperature (32°C) than the wild type parent. The ΔBbmsn2 mutant also displayed a pH‐dependent growth phenotype, with little growth seen at pH < 5.0 but, better growth at alkaline conditions (pH > 8.0). Unexpectedly, a pH‐dependent deregulation of a red pigment, identified as oosporein, was seen in the ΔBbmsn2 mutant. The ΔBbmsn2 strain was impaired in virulence in both topical and intrahaemocoel injection bioassays against Galleria mellonella. ΔBbmsn2 proliferation in the host haemolymph and conidiation on the host cadaver was reduced. These data indicate that Bbmsn2 acts as a negative regulator of oosporein production and contributes to virulence and growth in response to external pH in B. bassiana.